Self-repairing super-hydrophobic flame-retardant composite material, preparation method and application thereof

CN122978495APending Publication Date: 2026-10-27CHENGDU XIAODU DI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611274331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]然而,深入分析可以发现,杜晓声团队的技术方案存在以下三个尚未被突破的根本性技术瓶颈:第一,涂层划伤后超疏水性能不可逆失效,因为BMI基体是刚性热固性网络,不具备分子链重排和形貌修复的能力;第二,材料退役后不可回收,BMI基体的高度交联热固性网络决定了废弃后只能填埋或焚烧,无法实现闭环循环利用;第三,功能模块割裂,阻燃功能(含磷侧基2D-M)、超疏水功能(v-SiO2/PDMS复合粒子)、网络拓扑特征(刚性交联)由三种彼此独立的化学机制分别提供,缺乏有机协同

Benefits of technology

[0029](1)原理创新:本发明首次提出“二硫键与可交换酯键温度分区双动态协同”机制。在单一动态共价网络中同时引入二硫键和可交换酯键,二硫键在130-150℃激活,主导表面微纳结构快速修复,可交换酯键在80-200℃激活,主导网络拓扑重排和整体再加工,使同一网络中两种动态键各自承担不同尺度的动态响应任务。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978495A_ABST
    Figure CN122978495A_ABST
Patent Text Reader

Abstract

The application discloses a kind of self-repairing super-hydrophobic flame-retardant composite material and its preparation method and application, the composite material is by dynamic covalent crosslinking matrix network and by free radical addition reaction covalent anchoring on the surface of matrix network super-hydrophobic function layer is constituted;Dynamic covalent crosslinking matrix network is the side group phosphorus-containing bismaleimide vitreous network containing disulfide bond and exchangeable ester bond simultaneously.The composite material simultaneously introduces disulfide bond and exchangeable ester bond in single dynamic covalent network, disulfide bond is activated at 130-150 DEG C, and exchangeable ester bond is activated at 180-200 DEG C, and the whole reprocessing is dominated by network topology rearrangement and rapid repair of surface micro-nano structure.The application realizes the system integration and coordination of four functions of flame-retardant, super-hydrophobic, self-repairing and rework on single dynamic chemical platform for the first time, and has good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a self-healing superhydrophobic flame-retardant composite material, its preparation method, and its application. Background Technology

[0002] Superhydrophobic surfaces have always been a research hotspot in surface engineering due to their unique wetting properties in areas such as self-cleaning, anti-icing, drag reduction, and antifouling. Combining superhydrophobic properties with flame-retardant functions in a single material system to obtain integrated materials that possess both special wetting properties and fire safety protection functions shows great market potential in applications with stringent requirements for both safety and environmental durability, such as building curtain walls, anti-flashover coatings for power facilities, conformal coatings for electronic devices, and antifouling coatings for marine equipment.

[0003] In recent years, several technological approaches have emerged in the field of superhydrophobic flame-retardant composite materials. One approach involves nanoparticle-polymer blends, which achieve multifunctional composites by physically dispersing flame-retardant nanoparticles and hydrophobic micro / nanoparticles in low surface energy polymers. However, the functional particles and polymers rely solely on physical interactions for bonding, resulting in coatings whose durability under mechanical wear or chemical corrosion conditions generally fails to meet long-term engineering service requirements. Another approach utilizes layer-by-layer self-assembly and multi-level pore construction techniques to achieve multi-level functional integration by alternately depositing flame-retardant and hydrophobic layers on the substrate surface. However, the interlayer interface bonding is primarily based on physical interactions, and the overall environmental stability and mechanical durability of the coating still need improvement.

[0004] The paper "Covalently bonded superhydrophobic coating on intrinsically flame-retardant bismaleimide substrate with outstanding mechanical and environmental durability" discloses a composite material system in which a covalently anchored superhydrophobic coating is constructed on intrinsically flame-retardant bismaleimide (BMI). The core contribution of this work is that, through a "semi-cured substrate-covalent grafting" interface strategy, vinyl-functionalized silica / polydimethylsiloxane (v-SiO2 / PDMS) composite particles are chemically grafted onto the surface of a semi-cured BMI substrate to prepare a composite material that combines superhydrophobicity (water contact angle 166°) and intrinsic flame retardancy (UL-94 V-0). It also confirms that the interfacial covalent bonding effectively delays the coating's detachment failure under mechanical wear conditions.

[0005] However, in-depth analysis reveals three fundamental technical bottlenecks in Du Xiaosheng's team's solution that have yet to be overcome: First, the superhydrophobic properties of the coating become irreversibly damaged after scratches because the BMI matrix is ​​a rigid thermosetting network that lacks the ability to rearrange molecular chains and repair morphology. Second, the material is not recyclable after decommissioning because the highly cross-linked thermosetting network of the BMI matrix means that it can only be landfilled or incinerated after disposal, making closed-loop recycling impossible. Third, the functional modules are fragmented; the flame-retardant function (phosphorus-containing 2D-M side groups), the superhydrophobic function (v-SiO2 / PDMS composite particles), and the network topology characteristics (rigid cross-linking) are provided by three independent chemical mechanisms, lacking organic synergy.

[0006] How to overcome the two technical bottlenecks of "unrepairable functional layer damage and non-recyclable matrix" brought about by rigid thermosetting matrices while maintaining the superhydrophobic durability advantage of interfacial covalent anchoring, and how to achieve system integration and synergistic unity of the four functions of flame retardancy, superhydrophobicity, self-healing and reprocessability on a single dynamic chemical platform, is an urgent problem to be solved in this field. Summary of the Invention

[0007] The purpose of this invention is to solve the above problems and provide a self-healing superhydrophobic flame-retardant composite material, its preparation method and application. This composite material, while maintaining the superhydrophobic durability advantage given by interfacial covalent anchoring, integrates four functions in a single material system: superhydrophobicity, intrinsic flame retardancy, surface self-healing and bulk reprocessability, and achieves chemical synergy and system unity among the functional modules.

[0008] To achieve the above objectives, on the one hand, the present invention provides a self-healing superhydrophobic flame-retardant composite material, which is composed of a dynamic covalently cross-linked matrix network and a superhydrophobic functional layer covalently anchored to the surface of the dynamic covalently cross-linked matrix network through a free radical addition reaction. The dynamic covalently cross-linked matrix network is a phosphorus-containing bismaleimide glassy network containing both disulfide bonds and exchangeable ester bonds. The disulfide bonds can undergo reversible exchange reactions in the temperature range of 130-150℃, and the exchangeable ester bonds can undergo transesterification reactions in the temperature range of 180-200℃.

[0009] The aforementioned self-healing superhydrophobic flame-retardant composite material features a phosphorus-containing bismaleimide glassy network with a bismaleimide backbone, phosphorus-containing flame-retardant groups introduced into the side chains, and a network backbone containing both disulfide bonds and exchangeable ester bonds—two types of dynamic covalent bonds. This phosphorus-containing thermosetting polymer network structure possesses high glass modulus, high temperature resistance, intrinsic flame retardancy, and self-healing and reprocessable properties imparted by dynamic bond exchange. Preferably, the dynamic covalently crosslinked matrix network is prepared by thermal copolymerization using 4,4′-bismaleimide-diphenylmethane, 2,2′-diallylbisphenol A, bis(4-aminophenyl)disulfide, bis(4-aminophenyl)adipate, and phosphorus-containing reactive monomers as raw materials. The matrix network of this invention employs a "dual dynamic bond" design, simultaneously introducing both disulfide bonds (SS) and exchangeable ester bonds into a single dynamic covalent network. The disulfide bond has a bond energy of approximately 240 kJ / mol, and a reversible bond-breaking and recombination exchange reaction can occur in the relatively mild temperature range of 130-150℃. This drives local network topological rearrangement in the scratched area, filling the scratch morphology, while simultaneously exposing low surface energy components to the surface, restoring the superhydrophobic function. The activation energy of the exchangeable ester bond is significantly higher than that of the disulfide bond, and it undergoes transesterification in the higher temperature range of 180-200℃, driving macroscopic network flow and overall reshaping to achieve the reprocessing and recycling of waste powder. The two dynamic bonds independently dominate the response behavior within their respective temperature ranges without interfering with each other, together forming a complete chemical basis supporting the dynamic response at both the surface repair and bulk rearrangement levels. Phosphorus-containing reactive monomers are covalently fixed to the network backbone, achieving UL-94 V-0 intrinsic flame retardancy.

[0010] The aforementioned self-healing superhydrophobic flame-retardant composite material uses phosphorus-containing reactive monomers, which are compounds whose molecular structure simultaneously contains phosphorus and active groups capable of participating in polymerization reactions. These monomers are used to introduce phosphorus flame-retardant units into the polymer backbone or side chains via copolymerization, thus combining flame-retardant functionality with material mechanical / thermal stability. In this invention, the active group of the phosphorus-containing reactive monomer is a maleimide double bond, specifically a bismaleimide monomer with phosphorus-containing side groups. Preferably, the phosphorus-containing reactive monomer is prepared from DOPO, 4,4′-diaminobenzophenone, N,N-dimethylformamide, maleic anhydride, and a catalyst via a condensation reaction of DOPO and 4,4′-diaminobenzophenone in N,N-dimethylformamide to obtain a phosphorus-containing diamine intermediate. This intermediate is then reacted with maleic anhydride under catalysis to obtain the final product. The molar percentages of bis(4-aminophenyl)disulfide and bis(4-aminophenyl)adipate are 2-10% and 2-8%, respectively; the mass percentage of the phosphorus-containing reactive monomer is 15-20%.

[0011] The aforementioned self-healing superhydrophobic flame-retardant composite material features a superhydrophobic functional layer that is a surface-modified vinyl-functionalized SiO2 / PDMS coating with fluorocarbon coating. This coating is chemically grafted onto a side-group phosphorus-containing bismaleimide glassy network via interfacial covalent crosslinking. Vinyl-functionalized silica / polydimethylsiloxane composite particles are chemically anchored to the surface of the dynamic network using a "semi-curing-covalent grafting" interfacial technique, forming a complete chemical bond connection from the surface superhydrophobic layer to the bulk network. Surface fluorocarbon modification imparts superhydrophobic properties (contact angle ≥162°).

[0012] On the other hand, the present invention also provides a method for preparing a self-healing superhydrophobic flame-retardant composite material, comprising the following steps:

[0013] S1. Synthesis of Dynamically Covalently Crosslinked Matrix Networks

[0014] 4,4′-bismaleimide diphenylmethane, 2,2′-diallylbisphenol A, bis(4-aminophenyl) disulfide, bis(4-aminophenyl) adipate, phosphorus-containing reactive monomers and transesterification catalysts were mixed in a set ratio and subjected to a semi-curing prepolymerization reaction at 115℃-125℃ for 2-4 hours under nitrogen protection to obtain a semi-curing dynamic covalent crosslinked prepolymer containing active maleimide double bonds;

[0015] Preparation of S2, vinyl-functionalized SiO2 / PDMS composite particles

[0016] Vinyl-functionalized silica is obtained by reacting nano-silica with vinyltrimethoxysilane under alkaline conditions in a predetermined ratio. This silica is then dispersed in vinyl-terminated polydimethylsiloxane, and a platinum catalyst is added to prepare a vinyl-functionalized SiO2 / PDMS composite particle slurry. Preferably, the mass ratio of nano-silica to vinyltrimethoxysilane is 5:0.5-1.5, and the solid content of the vinyl-functionalized SiO2 / PDMS composite particle slurry is 3-6 wt%.

[0017] S3. Synthesis of self-healing superhydrophobic flame-retardant composite materials

[0018] The slurry obtained in step S2 is sprayed onto the surface of the semi-cured prepolymer obtained in step S1 to obtain material A. Material A is then completely cured for 2-4 hours under a gradient temperature increase of 140-200℃, allowing the vinyl groups to undergo free radical addition copolymerization with the maleimide double bonds retained in the prepolymer to form covalent bonds. After curing, material B is obtained. Material B is then immersed in an ethanol solution of perfluorodecyltrimethoxysilane for surface fluorocarbon modification. After modification, the material is washed and dried to obtain a self-healing superhydrophobic flame-retardant composite material.

[0019] In the preparation method of the above-mentioned self-healing superhydrophobic flame-retardant composite material, in step S1, 4,4′-bismaleimide diphenylmethane (BMI) serves as the core crosslinking matrix, providing reactive maleimide double bonds and acting as the main source of crosslinking points for the system. After curing, it imparts excellent heat resistance, mechanical strength, and electrical insulation properties to the material. 2,2′-diallylbisphenol A acts as a chain extender, forming allyl side groups and retaining active double bonds. Bis(4-aminophenyl) disulfide introduces dynamic disulfide covalent bonds, dominating surface repair at 130-150℃. Bis(4-aminophenyl) adipate introduces exchangeable ester bonds, dominating reprocessing at 180-200℃. Phosphorus-containing reactive monomers are attached to the maleimide ring via DOPO nucleophilic addition, providing intrinsic flame-retardant side groups. The proportions of each material can be set according to theoretical equivalence. Preferably, the mass ratio of 4,4′-bismaleimide diphenylmethane to 2,2′-diallylbisphenol A is 1:0.3-0.5, the molar percentages of bis(4-aminophenyl) disulfide and bis(4-aminophenyl) adipate in the prepolymer are 2-10% and 2-8%, respectively; and the mass percentage of the phosphorus-containing reactive monomer in the prepolymer is 15-20%. Further, 2,2′-diallylbisphenol A is generally 30%-50% of the mass of 4,4′-bismaleimide diphenylmethane (BMI) (48% in Example 1).

[0020] In the preparation method of the above-mentioned self-healing superhydrophobic flame-retardant composite material, in step S1, the transesterification catalyst is preferably at least one of dibutyltin dilaurate, tetrabutyl titanate, or zinc acetylacetonate, and the amount added is 0.1-0.5 wt% of the total mass of the five raw materials in step S1: 4,4′-bismaleimide diphenylmethane, 2,2′-diallylbisphenol A, bis(4-aminophenyl) disulfide, bis(4-aminophenyl) adipate, and phosphorus-containing reactive monomer.

[0021] In the preparation method of the above-mentioned self-healing superhydrophobic flame-retardant composite material, in step S2, the mass ratio of nano-silica to vinyltrimethoxysilane is 5:0.5-1.5, and the solid content of the vinyl-functionalized SiO2 / PDMS composite particle slurry is 3-6 wt%.

[0022] In the preparation method of the above-mentioned self-healing superhydrophobic flame-retardant composite material, the gradient heating conditions in step S3 are: 120℃ for 1-2 h, 140℃ for 1-2 h, 160℃ for 1-2 h, and 180℃ for 1-2 h, with a heating rate ≤2℃ / min. The specific conditions for fluorocarbon modification can be selected according to conventional operating parameters in the field.

[0023] The preparation method of the above-mentioned self-healing superhydrophobic flame-retardant composite material, wherein the preparation method of the phosphorus-containing reactive monomer is as follows: DOPO and 4,4′-diaminobenzophenone are dissolved in solvent A at a molar ratio of 1.8-2.2:1, and reacted at 110℃-130℃ to synthesize intermediate 2D-A. After cooling, maleic anhydride is added to intermediate 2D-A at a molar ratio of 1:1.8-2.2, and an addition reaction is carried out at 75℃-90℃ under the action of a catalyst. After the reaction is completed, precipitation, filtration, washing, and drying are performed to obtain the phosphorus-containing reactive monomer. The proportions of each material can be set according to the theoretical equivalent. Solvent A can be a conventional solvent in the art; in this invention, N,N-dimethylformamide (DMF) is preferred. The amount of solvent used can be the conventional amount. Sodium acetate is preferred as the catalyst.

[0024] In addition, the present invention also provides an application of the above-mentioned composite material in building exterior wall protective coatings, power facility anti-flashover coatings, electronic equipment conformal coatings, marine equipment anti-fouling coatings, or aerospace composite materials.

[0025] The core inventive concept of this invention lies in no longer viewing self-healing and reprocessability as independent "additional functions," but rather as a systematic extension of the inherent characteristics of dynamic covalent networks. It proposes for the first time a novel functional integration paradigm of "temperature-zoned dual dynamic synergy"—simultaneously constructing disulfide bonds and exchangeable ester bonds within a single BMI-based dynamic covalent network, fully utilizing the essential differences between the two in bond exchange activation energy and exchange rate to achieve functional division and hierarchical synergy of the two dynamic bonds within the same network. Figure 1 The diagram shows the design principle of the "temperature-zoned dual-dynamic synergistic" composite material of this invention. The diagram illustrates a three-layer structure: the bottom layer is a bulk dynamic covalent matrix layer (yellow area), containing disulfide bonds (SS, red short lines), exchangeable ester bonds (green wavy lines), and phosphorus-containing flame-retardant side groups (blue spheres); the middle layer is an interfacial covalent grafting layer (purple dashed area), labeled "free radical addition copolymerization"; the top layer is a surface superhydrophobic functional layer, containing v-SiO2 nanoparticles (gray small circles), a PDMS framework (gray mesh), and PFDTS fluorocarbon modification (light blue thin layer). Figure 2 The diagram shows a temperature-zoned dual-dynamic synergistic mechanism: disulfide bond exchange reaction – two SS bonds are homolytically cleaved to generate sulfur free radicals, which then recombine to form new bonds; ester exchange reaction – ester groups exchange with hydroxyl groups, and network connection points are redistributed.

[0026] Disulfide bonds, due to their low bond energy (approximately 240 kJ / mol), can undergo reversible exchange reactions in a relatively mild temperature range of 130℃-150℃, driving local network topological rearrangement in surface scratch areas to rapidly restore micro / nano morphology. Exchangeable ester bonds, due to their higher activation energy, undergo transesterification reactions in a higher temperature range of 180℃-200℃, driving macroscopic network flow and overall reshaping to achieve the reprocessing and recycling of waste powder. These two dynamic bonds dominate the response behavior within their respective temperature windows without interfering with each other, together forming a complete chemical basis supporting the dynamic responses at both the "surface repair" and "bulk rearrangement" levels.

[0027] Meanwhile, this invention further integrates the surface superhydrophobic functional layer and the bulk dynamic network through covalent bonding. Utilizing the characteristic that the maleimide double bonds in BMI resin can undergo free radical addition copolymerization with vinyl groups during thermosetting, the surface v-SiO2 / PDMS composite particles are firmly anchored to the surface of the dynamic network by chemical covalent bonds during the curing process through a two-step "semi-curing-complete curing" method, forming a complete chemical transport chain of "surface functional layer - interface covalent bond - bulk dynamic network".

[0028] The self-healing superhydrophobic flame-retardant composite material, its preparation method, and its application provided by this invention have the following beneficial effects:

[0029] (1) Innovative Principle: This invention proposes for the first time a "dual dynamic synergy mechanism of temperature partitioning of disulfide bonds and exchangeable ester bonds". Disulfide bonds and exchangeable ester bonds are introduced simultaneously into a single dynamic covalent network. Disulfide bonds are activated at 130-150℃, which dominates the rapid repair of surface micro and nano structures. Exchangeable ester bonds are activated at 80-200℃, which dominate the network topology rearrangement and overall reprocessing. This allows the two dynamic bonds in the same network to undertake dynamic response tasks at different scales.

[0030] (2) Collaborative Innovation: Through the "semi-curing-covalent grafting" interface technology, the superhydrophobic functional layer and the bulk dynamic network form chemical bonds, realizing an unexpected synergistic effect of "bulk network rearrangement driving surface repair". Specifically, through the "semi-curing-covalent grafting" interface technology, vinyl-functionalized silica / polydimethylsiloxane composite particles are chemically anchored to the surface of the dynamic network, forming a full chemical bond connection from the surface superhydrophobic layer to the bulk network. Phosphorus-containing reactive monomers are fixed to the network backbone by covalent bonds, achieving UL-94 V-0 intrinsic flame retardancy; surface fluorocarbon modification imparts superhydrophobic properties (contact angle ≥162°).

[0031] (3) Qualitative change in functional integration: This invention is the first to realize the system integration of four functions, namely flame retardancy, superhydrophobicity, self-healing and reprocessability, on a single dynamic chemical platform. Furthermore, the chemical synergy of functions is achieved through covalent anchoring interfaces rather than physical superposition, providing a complete solution for the “repairable, recyclable and serviceable” green high-performance polymer materials.

[0032] (4) Overall, the preparation method of the present invention is simple, highly operable, and suitable for mass production. The composite material has good application prospects in the fields of building exterior wall protective coating, power facility anti-flashover coating, electronic equipment three-proof coating, marine equipment anti-fouling coating or aerospace composite material. Attached Figure Description

[0033] Figure 1 This is a schematic diagram of the "temperature zone dual dynamic synergy" design principle of the composite material of this invention;

[0034] Figure 2 This is a schematic diagram of a temperature-zoned dual-dynamic collaborative mechanism;

[0035] Figure 3 These are the FTIR and Raman spectra of the sample from Example 1;

[0036] Figure 4 This is a micro / nano structure diagram of the sample surface from Example 1, in which... Figure 4 (a) is the original surface. Figure 4 (b) is a magnified view of the original surface. Figure 4 (c) shows the surface after scratching; Figure 4 (d) Surface after 50 minutes of repair at 140℃;

[0037] Figure 5 It is the HRR curve of the cone calorimeter for flame retardant performance;

[0038] Figure 6 This is a comparison chart of the water contact angle before and after surface self-healing;

[0039] Figure 7 It is a bar chart showing the recovery rate of mechanical properties and flame retardant properties before and after reprocessing; Detailed Implementation

[0040] The technical solutions of various embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are part of the present invention.

[0041] The raw materials involved in this invention can be prepared in-house or purchased from the market. The preparation methods of the raw materials involved in the following embodiments are shown in Tables 1 and 2. The specific preparation methods of the in-house raw materials will be described in detail in the specific embodiments.

[0042] Table 1. Components of the Dynamically Covalently Crosslinked Matrix Network

[0043] Components Brand / Model / Specification Function Description Source / Manufacturer 4,4′-Bismaleimide diphenylmethane (BDM) Industrial grade, purity ≥98% Containing active maleimide double bonds, constructing the main crosslinking network Sinopharm Group 2,2′-Dearly allyl bisphenol A (DBA) Industrial grade, purity ≥96% Chain extender, forming allyl side groups, retaining active double bonds Shanghai McLean bis(4-aminophenyl) disulfide (DTDA) self made Introducing dynamic disulfide bonds to dominate surface repair at 130-150℃ self made bis(4-aminophenyl) adipate (DPA) self made Introducing exchangeable ester bonds, with reprocessing dominated at 180-200℃. self made Phosphorus-containing reactive monomer 2D-M self made The intrinsic flame-retardant side group is attached to the maleimide ring via DOPO nucleophilic addition. self made Dibutyltin dilaurate (DBTDL) Analytical Pure Ester exchange catalyst, reducing the activation energy of ester bond exchange. Aladdin

[0044] Table 2 Components of the superhydrophobic functional layer on the surface

[0045] Components Brand / Model / Specification Function Description Source / Manufacturer Hydrophobic nano silica Evonik AEROSIL R812S Constructing a micro / nano dual-scale rough structure with a specific surface area of ​​approximately 220 m² / g Evonik Vinyltrimethoxysilane (VTMS) Momentive Silquest A-171 Vinyl functionalization modification of silica surface, participating in covalent grafting Momentive Vinyl-terminated polydimethylsiloxane (V-PDMS) Dow Corning DMS-V31 Low surface energy organosilicon components participate in free radical addition copolymerization Dow Chemicals Platinum-divinyltetramethyldisiloxane complex Karstedt catalyst, 2% platinum content Catalytic hydrosilylation to regulate the degree of crosslinking of V-PDMS Sigma Aldridge 1H,1H,2H,2H-Perfluorodecyltrimethoxysilane (PFDTS) 98% purity Fluorocarbon low surface energy modification imparts superhydrophobic properties. Sigma Aldridge

[0046] Example 1

[0047] Example 1 provides a self-healing superhydrophobic flame-retardant composite material and its preparation method. The composite material consists of a dynamically covalently cross-linked matrix network and a superhydrophobic functional layer covalently anchored to the surface of the dynamically covalently cross-linked matrix network via free radical addition reactions. The dynamically covalently cross-linked matrix network is a phosphorus-containing bismaleimide glassy network containing both disulfide bonds and exchangeable ester bonds. The disulfide bonds can undergo reversible exchange reactions in the temperature range of 130-150℃, and the exchangeable ester bonds can undergo transesterification reactions in the temperature range of 180-200℃.

[0048] The dynamically covalently crosslinked matrix network is prepared by thermal copolymerization using 4,4′-bismaleimide diphenylmethane, 2,2′-diallyl bisphenol A, bis(4-aminophenyl) disulfide, bis(4-aminophenyl) adipate, and DOPO-based phosphorus-containing reactive monomers as raw materials. The superhydrophobic functional layer is a vinyl-functionalized SiO2 / PDMS coating with fluorocarbon modification on the surface, which is chemically grafted onto the side-group phosphorus-containing bismaleimide glass network through interfacial covalent crosslinking.

[0049] The preparation method of the above-mentioned self-healing superhydrophobic flame-retardant composite material specifically includes the following steps:

[0050] S1. Synthesis of Dynamically Covalently Crosslinked Matrix Networks

[0051] S11. Synthesis of flexible diamine monomers: ① Synthesis of bis(4-aminophenyl) disulfide (DTDA): 12.5 g of 4-aminophenylthiophenol was dissolved in 100 mL of anhydrous ethanol, and 5.5 mL of 30% hydrogen peroxide aqueous solution was slowly added dropwise at room temperature. After the addition was complete, the reaction was stirred for 2 hours. The mixture was filtered, and the filter cake was washed with deionized water and dried under vacuum to obtain bis(4-aminophenyl) disulfide (DTDA) with a yield of approximately 85%. ② Synthesis of bis(4-aminophenyl) adipate (DPA): Under nitrogen protection, 11.1 g of 4-nitrophenol and 8.0 g of anhydrous pyridine were added to 150 mL of anhydrous ethanol. In anhydrous tetrahydrofuran, 7.3 g of adipic acid chloride was added in portions under an ice-water bath. After the addition was complete, the mixture was heated to room temperature and stirred for 4 hours. After the reaction was completed, the pyridine hydrochloride precipitate was removed by filtration. The filtrate was concentrated by rotary evaporation to precipitate a solid, which was recrystallized from anhydrous ethanol to obtain bis(4-nitrophenyl)adipate. Subsequently, the obtained bis(4-nitrophenyl)adipate was dissolved in 150 mL of anhydrous ethanol, and 0.5 g of 10% Pd / C catalyst was added. The mixture was stirred at room temperature for 12 hours under a hydrogen atmosphere. The catalyst was removed by filtration, and the filtrate was concentrated and dried under vacuum to obtain bis(4-aminophenyl)adipate (DPA) in approximately 76% yield.

[0052] Synthesis of S12, Phosphorus-containing reactive monomer 2D-M: Under nitrogen protection, 21.6 g of DOPO and 10.6 g of 4,4′-diaminobenzophenone were dissolved in 200 mL of N,N-dimethylformamide (DMF) and reacted at 120 °C for 8 hours to obtain intermediate 2D-A. After cooling, 9.8 g of maleic anhydride and 0.8 g of sodium acetate were added, and the mixture was reacted at 80 °C for 4 hours. After cooling, the precipitate was poured into deionized water, filtered, washed, and dried to obtain a light yellow powder, namely the phosphorus-containing reactive monomer 2D-M, with an overall yield of approximately 82% and a melting range of 168-172 °C. Its molecular structure was confirmed by FTIR, ¹H NMR, and ³¹P NMR.

[0053] S13. Preparation of dynamic covalently cross-linked prepolymer: 25.0 g of 4,4′-bismaleimide diphenylmethane (BDM), 12.0 g of 2,2′-diallylbisphenol A (DBA), 2.5 g of bis(4-aminophenyl) disulfide (DTDA), 1.5 g of bis(4-aminophenyl) adipate (DPA), 7.0 g of phosphorus-containing reactive monomer 2D-M, and 0.15 g of dibutyltin dilaurate (DBTDL) were added to a reaction vessel, stirred and mixed evenly, and heated to 120°C under nitrogen protection and stirred for 2 hours to obtain a semi-cured dynamic covalently cross-linked prepolymer containing active maleimide double bonds.

[0054] S2, Preparation of vinyl-functionalized silica / PDMS composite particles

[0055] S21. Surface vinyl functionalization of nano-silica: Weigh 5.0 g of nano-silica and disperse it in 50 mL of anhydrous ethanol, then sonicate for 30 minutes. Add 1.0 g of VTMS and 0.5 g of deionized water, and adjust the pH to 9-10 by adding ammonia dropwise. Stir the reaction at room temperature for 6 hours. After centrifugation and washing, dry under vacuum at 60°C for 12 hours to obtain vinyl-functionalized silica (v-SiO2), with a yield of approximately 92%.

[0056] S22. Preparation of composite particles: Disperse 4.0 g of v-SiO2 in 100 g of V-PDMS, add 0.05 g of Karstedt catalyst and dilute with an appropriate amount of anhydrous ethanol to prepare a vinyl-functionalized SiO2 / PDMS composite particle slurry with a solid content of about 4.0 wt%.

[0057] S3. Synthesis of self-healing superhydrophobic flame-retardant composite materials

[0058] S31. Pre-forming of semi-cured substrate: Pour the semi-cured dynamic covalent cross-linked prepolymer prepared in step S13 into a mold, remove air bubbles, and pre-cur at 120°C for 2 hours to obtain a semi-cured sheet.

[0059] S32, Covalent anchoring of the superhydrophobic functional layer: The v-SiO2 / PDMS composite particle slurry prepared in step S22 is uniformly applied to the surface of the semi-cured sheet by a two-component spraying method.

[0060] S33. Gradient thermosetting and covalent anchoring network construction: The sprayed material is cured by gradient temperature increase from 120℃ / 1h to 140℃ / 1h to 160℃ / 1h to 180℃ / 1h, which causes maleimide double bonds to undergo free radical addition copolymerization with vinyl groups, forming a complete chemical transport chain of "surface functional layer - interface covalent bond - bulk dynamic network".

[0061] S34, Fluorocarbon low surface energy modification: The cured material is immersed in an ethanol solution of PFDTS with a PFDTS modification concentration of 2 wt%, left to stand at room temperature for 12 hours, then removed and washed with ethanol, and vacuum dried at 60℃ for 2 hours to obtain a self-healing superhydrophobic flame retardant composite material.

[0062] The triggering conditions for the self-healing and reprocessable behavior of this composite material are as follows:

[0063] Superhydrophobic surface repair: When the coating surface loses its superhydrophobicity due to mechanical wear or scratches from sharp objects, place the material in an oven at 130-150℃ and heat for 30-60 minutes. The water contact angle recovery rate is ≥96%.

[0064] Overall reprocessing and recycling: When materials reach the end of their service life and need to be recycled, the waste materials are crushed to below 100 mesh and hot-pressed at 180-200℃ and 5-10 MPa for 15-30 minutes. The mechanical property recovery rate is ≥86%, and the flame retardant rating is maintained above V-1.

[0065] like Figure 3 The image shows the FTIR and Raman spectra of the composite material sample prepared in Example 1, which show the presence of disulfide bonds (SS), ester bonds, phosphorus-containing side groups, and characteristic peaks of siloxanes.

[0066] like Figure 4 The image shown is a micro / nano structure diagram of the surface of the composite material sample prepared in Example 1. Figure 4 (a) / (b) shows the original surface, where PDMS micro-skeleton (gray spherical particles with a diameter of about 2-5 μm) are uniformly distributed on the surface, and SiO2 nanoparticles (black dots with a diameter of 20-50 nm) are stacked on the micro-skeleton to form a typical micro-nano dual-scale rough structure. Figure 4 (c) The surface after scratching: a scratch about 15 μm wide is shown, and the micro-nano structure is destroyed. Figure 4 (d) Surface after 50 minutes of repair at 140℃: scratches disappeared and micro-nano structures were restored, indicating that disulfide bond-driven local network rearrangement effectively repaired the surface morphology.

[0067] Comparative Example 1

[0068] This comparative example prepares a composite material containing only disulfide bonds in a dynamic network (without ester bonds). It is based on Example 1, omitting DPA (exchangeable ester bond monomer), while keeping other components and processes unchanged. It is designated as Group A.

[0069] Comparative Example 2

[0070] This comparative example prepared a dynamic network containing only ester bonds (without disulfide bonds). It omitted DTDA (disulfide bond monomer) from Example 1, while keeping other components and processes unchanged. It is referred to as Group B.

[0071] Example 2

[0072] Compared with Example 1, this embodiment sets a phosphorus-containing reactive monomer 2D-M content gradient of 0, 10, 15, 20, 25, and 30 wt% (based on the total mass of the matrix raw materials) in Example 1, and adjusts other components accordingly. Specifically, the total mass of each group of matrix raw materials (BDM, DBA, DTDA, DPA, and 2D-M) is controlled at 48.0 g, with DTDA fixed at 2.5 g, DPA fixed at 1.5 g, and transesterification catalyst DBTDL fixed at 0.15 g. The 2D-M content is 0, 4.8, 7.2, 9.6, 12.0, and 14.4 g, respectively. The BDM and DBA content is adjusted accordingly at a mass ratio of 25:12, i.e., the BDM content is 29.7, 26.5, 24.9, 23.2, 21.6, and 20.0 g, respectively. The DBA dosages were 14.3, 12.7, 11.9, 11.2, 10.4, and 9.6 g, respectively, with all other process parameters remaining identical. The effect of the phosphorus-containing reactive monomer 2D-M on flame retardant properties is shown in Table 3.

[0073] Table 3. Effect of 2D-M on flame retardant properties

[0074] 2D-M content (wt%) LOI (%) UL-94 rating PHRR reduction rate (%) 0 23.4 Variable benchmark 10 28.6 V-2 31.5 15 34.8 V-0 58.2 20 36.2 V-0 67.8 25 36.5 V-0 69.3 30 36.8 V-0 70.1

[0075] As shown in Table 3, the UL-94 V-0 rating is achieved when the content of the phosphorus-containing reactive monomer 2D-M is ≥15 wt%. It should be noted that when the 2D-M content is further increased to 25-30 wt%, the composite material can still achieve a V-0 rating, but the improvement in flame retardant performance becomes more gradual (LOI increases only from 36.2% at 20 wt% to 36.8%, and the PHRR reduction rate increases only from 67.8% to 70.1%). Excessive phosphorus-containing reactive monomers can lead to excessively high crosslinking density in the matrix, increased material brittleness, and a significant decrease in elongation at break. Simultaneously, the viscosity of the semi-cured prepolymer increases significantly, which is detrimental to the uniform spreading and covalent anchoring of the composite particle slurry on the matrix surface, and also increases the raw material cost accordingly. Considering the balance between flame retardant performance, mechanical properties, processing performance, and cost, the preferred mass percentage of the phosphorus-containing reactive monomer in this invention is 15-20 wt%. Figure 5 The image shows the HRR curve of the cone calorimeter for flame retardant performance. (From...) Figure 5 It can be seen that the peak heat release rate of the composite material sample prepared in Example 1 (about 98 kW / m²) is much lower than that of the natural BMI (about 380 kW / m²) and the ester bond network only (about 280 kW / m²).

[0076] The performance of the composite material sample prepared in Example 1 will be tested and verified below.

[0077] (1) Surface self-healing function verification

[0078] Scratches approximately 10-20 μm wide were made on the sample surface using a scalpel, and the sample was then heated at 140°C for 50 minutes. Figure 6 As shown, the water contact angle recovered from 125.3° to 156.8° after repair, a recovery rate of 96.5%. Optical microscopy showed that the scratches had essentially disappeared.

[0079] (2) Verification of overall reprocessing performance

[0080] The sample was pulverized to below 100 mesh, hot-pressed at 190℃ and 8 MPa for 20 minutes, and then molded. For example... Figure 7 As shown, after reprocessing, the tensile strength recovery rate was 86.3%, the flexural strength recovery rate was 86.6%, the LOI retention rate was 95.5%, and the UL-94 rating was maintained at V-1.

[0081] (3) Durability verification of covalent anchoring interface

[0082] A covalently anchored group (S1, the sample prepared in Example 1) and a physical adsorption control group (C0, sprayed after the substrate was fully cured) were set up. After 60 sandpaper rubbing cycles, the WCA of S1 was 154.8° (a decrease of 7.5°), and that of C0 was 112.3° (a decrease of 42°). After 60 tape peeling cycles, the WCA of S1 was 156.3°, and that of C0 was 108.6°. The interface failure cycle of S1 was >60 cycles, while that of C0 showed flaking after about 30 cycles.

[0083] (4) Temperature zone control verification (including Comparative Example 1 and Comparative Example 2)

[0084] Three control groups were set up: Comparative Example 1 (Group A): disulfide bonds only (no DPA); Comparative Example 2 (Group B): ester bonds only (no DTDA); and the present invention (Group C): coexistence of double bonds (S1). The repair / reprocessing behavior of the three groups of samples was tested at two temperature conditions: 140℃ and 190℃. The repair efficiency test method was as follows: scratches 10-20 μm wide and approximately 5 mm long were made on the sample surface, and the contact angle recovery rate of the scratched area was tested after treatment at the specified temperature for 60 minutes. The reprocessing effect evaluation method was as follows: the sample was crushed and then hot-pressed at the same temperature (190℃ group), and the tensile strength recovery rate after reprocessing was tested. The test results are shown in Table 4.

[0085] Table 4. Verification results of temperature zone control

[0086] Test conditions Comparative Example 1 (Group A, disulfide bonds only) Comparative Example 2 (Group B, ester bonds only) This invention (Group C, double bond coexistence) WCA recovery rate (%) after repair at 140℃ 96.2 69.8 96.5 Tensile strength recovery rate (%) after reprocessing at 190℃ 49.4 85.6 86.3

[0087] Table 4 shows that: when only disulfide bonds are present, the low-temperature repair efficiency is high (96.2%), but the reprocessing recovery rate is extremely low (49.4%); when only ester bonds are present, the reprocessing recovery rate is high (85.6%), but the low-temperature repair efficiency is insufficient (69.8%); when both bonds coexist, both indicators reach their optimal levels (96.5% and 86.3%). This proves that both dynamic bonds are indispensable, and that temperature-zoned design is the key technical means to achieve optimal function.

[0088] (5) Life cycle carbon emission estimation

[0089] Using the preparation of 1 kg of material as a functional unit, the net carbon emission is approximately 1.00 kg CO2 eq, which is far lower than that of conventional flame-retardant BMI resin (approximately 6.8-8.5 kg CO2 eq).

[0090] In summary, the self-healing superhydrophobic flame-retardant composite material provided by this invention consists of a dynamic covalently cross-linked matrix network and a superhydrophobic functional layer covalently anchored to the surface of the matrix network via free radical addition reactions. The dynamic covalently cross-linked matrix network contains both disulfide bonds and exchangeable ester bonds. This composite material is based on temperature-zoned dual dynamic synergy. Disulfide bonds undergo reversible exchange reactions in the 130-150℃ temperature range, driving topological rearrangement of the surface micro / nano structures to achieve self-healing of the superhydrophobic functional layer, with a water contact angle recovery rate ≥95%. Exchangeable ester bonds undergo transesterification reactions in the 180-200℃ temperature range, driving macroscopic flow of the entire network to achieve hot-pressing reprocessing and recycling of waste materials, with a mechanical property recovery rate ≥85%. The two dynamic bonds independently dominate the response behavior within their respective temperature ranges without interfering with each other, jointly forming a complete chemical basis supporting the dynamic response at both the surface repair and bulk rearrangement levels. This fundamentally avoids the inherent problem of "functional coupling leading to mutual constraint" in a single dynamic bond network. This invention is the first to integrate four functions—flame retardancy, superhydrophobicity, self-healing, and reprocessability—within a dynamic double-bond network. Through a "semi-cured-covalent grafting" interface technology, the superhydrophobic functional layer forms chemical bonds with the bulk dynamic network, achieving an unexpected synergistic effect of "bulk network rearrangement driving surface repair." The composite material possesses the following comprehensive performance characteristics: initial water contact angle ≥160°, roll-off angle ≤5°; UL-94 vertical burning test V-0 rating; after scratch damage, water contact angle recovery rate ≥95% after heat treatment at 130-150℃ for 30-60 minutes; after waste material is crushed and remolded by hot pressing at 180-200℃ and 5-10 MPa for 15-30 minutes, tensile strength recovery rate ≥85%, limiting oxygen index retention rate ≥90%.

[0091] Those skilled in the art will recognize that the embodiments described herein are intended to help the reader understand the principles of the invention, and should be understood that the scope of protection of the invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific modifications and combinations based on the technical teachings disclosed in this invention without departing from the spirit of the invention, and these modifications and combinations are still within the scope of protection of this invention.

Claims

1. A self-healing superhydrophobic flame-retardant composite material, characterized in that: The composite material consists of a dynamic covalently cross-linked matrix network and a superhydrophobic functional layer covalently anchored to the surface of the dynamic covalently cross-linked matrix network via free radical addition reaction. The dynamic covalently cross-linked matrix network is a phosphorus-containing bismaleimide glassy network containing both disulfide bonds and exchangeable ester bonds. The disulfide bonds can undergo reversible exchange reactions in the temperature range of 130-150℃, and the exchangeable ester bonds can undergo transesterification reactions in the temperature range of 180-200℃.

2. The self-healing superhydrophobic flame-retardant composite material according to claim 1, characterized in that: The dynamic covalent crosslinked matrix network is prepared by thermal copolymerization using 4,4′-bismaleimide diphenylmethane, 2,2′-diallylbisphenol A, bis(4-aminophenyl) disulfide, bis(4-aminophenyl) adipate, and phosphorus-containing reactive monomers as raw materials.

3. The self-healing superhydrophobic flame-retardant composite material according to claim 2, characterized in that: The phosphorus-containing reactive monomer is prepared from DOPO, 4,4′-diaminobenzophenone, N,N-dimethylformamide, maleic anhydride, and catalyst. The phosphorus-containing diamine intermediate is prepared by condensation reaction of DOPO and 4,4′-diaminobenzophenone in N,N-dimethylformamide, and then prepared by addition reaction of the phosphorus-containing diamine intermediate with maleic anhydride under catalysis.

4. The self-healing superhydrophobic flame-retardant composite material according to claim 1, characterized in that: The superhydrophobic functional layer is a vinyl-functionalized SiO2 / PDMS coating with fluorocarbon modification on the surface, which is chemically grafted onto a bismaleimide glass network with phosphorus-containing side groups through interfacial covalent crosslinking.

5. A method for preparing a self-healing superhydrophobic flame-retardant composite material according to any one of claims 1-4, characterized in that: Includes the following steps: S1. Synthesis of Dynamically Covalently Crosslinked Matrix Networks 4,4′-bismaleimide diphenylmethane, 2,2′-diallylbisphenol A, bis(4-aminophenyl) disulfide, bis(4-aminophenyl) adipate, phosphorus-containing reactive monomers and transesterification catalysts were mixed in a set ratio and subjected to a semi-curing prepolymerization reaction at 115℃-125℃ for 2-4 hours under nitrogen protection to obtain a semi-curing dynamic covalent crosslinked prepolymer containing active maleimide double bonds; Preparation of S2, vinyl-functionalized SiO2 / PDMS composite particles Vinyl functionalized silica was obtained by reacting nano-silica with vinyltrimethoxysilane under alkaline conditions in a set ratio. It was then dispersed in vinyl-terminated polydimethylsiloxane and a platinum catalyst was added to prepare a vinyl functionalized SiO2 / PDMS composite particle slurry. S3. Synthesis of self-healing superhydrophobic flame-retardant composite materials The slurry obtained in step S2 is sprayed onto the surface of the semi-cured prepolymer obtained in step S1 to obtain material A. Material A is then completely cured for 2-4 hours under a gradient temperature increase of 140-200℃, allowing the vinyl groups to undergo free radical addition copolymerization with the maleimide double bonds retained in the prepolymer to form covalent bonds. After curing, material B is obtained. Material B is then immersed in an ethanol solution of perfluorodecyltrimethoxysilane for surface fluorocarbon modification. After modification, the material is washed and dried to obtain a self-healing superhydrophobic flame-retardant composite material.

6. The method for preparing the self-healing superhydrophobic flame-retardant composite material according to claim 5, characterized in that: In step S1, the mass ratio of 4,4′-bismaleimide diphenylmethane to 2,2′-diallylbisphenol A is 1:0.3-0.5, the molar percentages of bis(4-aminophenyl) disulfide and bis(4-aminophenyl) adipate are 2-10% and 2-8%, respectively, and the mass percentage of the phosphorus-containing reactive monomer is 15-20%. In step S1, the transesterification catalyst is selected from at least one of dibutyltin dilaurate, tetrabutyl titanate, or zinc acetylacetonate, and the amount added is 0.1-0.5 wt% of the total mass of the five raw materials: 4,4′-bismaleimide diphenylmethane, 2,2′-diallylbisphenol A, bis(4-aminophenyl) disulfide, bis(4-aminophenyl) adipate, and phosphorus-containing reactive monomer.

7. The method for preparing the self-healing superhydrophobic flame-retardant composite material according to claim 5, characterized in that: In step S2, the mass ratio of nano-silica to vinyltrimethoxysilane is 5:0.5-1.5, and the solid content of the vinyl-functionalized SiO2 / PDMS composite particle slurry is 3-6 wt%.

8. The method for preparing the self-healing superhydrophobic flame-retardant composite material according to claim 5, characterized in that: In step S3, the gradient heating conditions are: 120℃ for 1-2 hours, 140℃ for 1-2 hours, 160℃ for 1-2 hours, and 180℃ for 1-2 hours, with a heating rate ≤2℃ / min.

9. The method for preparing the self-healing superhydrophobic flame-retardant composite material according to claim 5, characterized in that: The preparation method of the phosphorus-containing reactive monomer is as follows: DOPO and 4,4′-diaminobenzophenone are dissolved in solvent A at a molar ratio of 1.8-2.2:1 and reacted at 110℃-130℃ to synthesize intermediate 2D-A. After cooling, maleic anhydride is added to intermediate 2D-A at a molar ratio of 1:1.8-2.2, and an addition reaction is carried out at 75℃-90℃ under the action of a catalyst. After the reaction is completed, the monomer is precipitated, filtered, washed, and dried to obtain the phosphorus-containing reactive monomer.

10. The application of the composite material as described in any one of claims 1-4 in building exterior wall protective coatings, power facility anti-flashover coatings, electronic equipment conformal coatings, marine equipment anti-fouling coatings, or aerospace composite materials.